Counter-Terrorism Policy in the ASEAN Region: Comparative Study of Malaysia and Indonesia - Ismed, Mohamad; Basuki , Basuki; Sinaulan, Ramlani Lina; Akkapin, Suphaporn (Journal Evidence Of Law, 2025)
This research aims to enrich the academic literature on counter-terrorism policies in the ASEAN region, focusing on a comparison between Malaysia and Indonesia. A qualitative method with a comparative study design is used to analyze the counter-terrorism policies of both countries to understand the differences, similarities, implementation, and effectiveness of the strategies applied. The results show that counter-terrorism policies in Malaysia and Indonesia reflect a strong commitment through comprehensive institutional structures, strict regulations, and diverse strategy implementations. In Indonesia, the policy tends to be repressive, influenced by domestic political dynamics and international pressures post the 2002 Bali Bombing. Malaysia adopts a more structured approach considering geographical and socio-political factors and utilizes strict legal frameworks like the Internal Security Act (ISA). Political factors are significant in policy formation in both countries, with Malaysia maintaining national stability through strong counter-terrorism policies. Social factors such as radicalization and extremism are also important, with Indonesia facing challenges from groups like Jamaah Islamiyah (JI) while Malaysia uses community-based approaches in its deradicalization programs. Comprehensive and coordinated strategies, increased inter-agency coordination, international cooperation, and integration of the private sector and media are needed to address the challenges.